Partial block to transcription of human adenovirus type 2 late genes in abortively infected monkey cells. - Johnston, J M (1985)
The block to efficient growth of human adenovirus in monkey cells results in depressed synthesis of late viral polypeptides. This is attributable in part to reduced steady-state levels of the encoding mRNAs. To identify the molecular basis for the reduction in late cytoplasmic mRNA, we compared nuclear RNA synthesis and cytoplasmic mRNA stability in monkey cells abortively infected with wild-type adenovirus serotype 2 (Ad2) and productively infected with the host-range mutant of Ad2, Ad2hr400, or productively infected with Ad2 plus simian virus 40. The half-lives of cytoplasmic mRNA from late gene families L3 (hexon), L4 (100K protein), and L5 (fiber) are similar in abortively and productively infected cells. However, the rate of RNA transcription is reduced 4- to 10-fold and correlates with the reductions in steady-state levels of cytoplasmic RNA. The depression in the rate of transcription cannot be accounted for by a difference in the amount of viral DNA present in abortively and productively infected cells. These studies also suggest that transcription from the major late promoter of Ad2 prematurely terminates in both monkey cells and human cells during the late phase of infection. Premature termination appears to be enhanced in abortive compared with productive infections of monkey cells and may contribute to the reduction in rates of nuclear RNA synthesis. Since the simian virus 40 T antigen or the adenovirus host-range mutant DNA-binding protein overcome these transcriptional impediments, these proteins are either directly or indirectly involved in transcriptional regulation of Ad2 late gene expression.